Agen Crosslink dalam Pembuatan Biomimetic Scaffold Sebagai Material Rekayasa Jaringan Tulang - Fitria Rahmitasari; Sularsih Sularsih (Jurnal Material Kedokteran Gigi, 2019)
Case of bone destruction such as socket of post-tooth extraction and periodontitis can cause pain and disrupt the function of mastication, so it takes a tissue engineering material in the form of biomimetic scaffold by mimicking the structure and the original function of bone. Material for bone tissue engineering that has grown widely include the use of collagen, gelatin, chitosan, and hydroxyapatite. These materials can be mutually combined using crosslink agents in the scaffold fabrication process. Determine the role of crosslink agents in the manufacture of biomimetic scaffolds as bone tissue engineering materials in the field of dentistry. Material in the scaffold fabrication is a polymer which can be modified by the incorporation of other polymers. Additionally, polysaccharides have abundant functional groups such as hydroxyl groups, amino groups and/or carboxylic acid groups, amenable to various types of chemical modifications. Modification with other polymers can be done by adding crosslink agents by irradiation or through chemical reactions. The role of a crosslink agent in a material modification can increase the material resistance to heat, light, other physical properties, and can increase the degree of dimensional stability and mechanical strength so these values are important to consider for the survival of cells in scaffolds at early time points. Different forms of crosslink agents can be utilized to obtain good biomimetic scaffold so that optimize the osteoconductivity properties of bone tissue engineering.